Math, asked by shrishti0864, 6 months ago

ye Bana ke do follow karuga
From the chapter factorization ​

Attachments:

Answers

Answered by AadityaSingh01
1

Answer:

0.86

Step-by-step explanation:

here, \frac{(5.3)^{2} - (3.3)^{2}}{(11.2)^{2} - (11.2) * (2.4) + (1.2)^{2}}

    ⇒ \frac{(5.3 + 5.3) (5.3 - 5.3)}{(11.2)^{2} - (11.2) * 2 * (1.2) + (1.2)^{2}}      [a^{2} - b^{2} = (a + b) (a - b) and a^{2} - 2ab + b^{2} = (a - b)^{2}]

    ⇒ \frac{8.6}{(11.2 - 1.2)^{2}}

    ⇒ \frac{8.6}{10}

    ⇒ 0.86

hope it will help you.

Similar questions